Low-Frequency Modulation Sensors Using Nanosecond Fluorophores - Lakowicz, Joseph R. (Anal Chem, 1998)
We describe a new approach to fluorescence sensing based on a mixture of fluorophores, one of which is sensitive to the desired analyte. If a long-lifetime analyte-insensitive fluorophore is mixed with a short-lifetime analyte-sensitive fluorophore, the modulation of the emission at conveniently low frequencies becomes equal to the fractional fluorescence intensity of the sensing fluorophore. Under these conditions, the modulation can be used to determine the analyte concentration. This can be used with any fluorophore that changes intensity in response to analyte and does not require the sensing fluorophore to display a change in lifetime. The feasibility of modulation-based sensing was demonstrated using mixtures of 6-carboxyfluorescein and [Ru 2,2′-(bipyridyl)(3)](2+) as a pH sensor and of the calcium probe Fluo-3 and [Ru 2,2′-(bipyridyl)(3)](2+) as a calcium sensor.